(untitled) (Vietnam Journal of Community Medicine, 2025)
City International General Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on all 262 clinical nurses. The study took place from January to July 2025 at Vinmec Times City International General Hospital. The research instrument was the KASRP, translated, validated, and standardized by Pham Van Truong and colleagues. Data were collected through guided self-administered questionnaires. Each correct answer was awarded one point, with a maximum total score of 41. Scores were categorized into three levels: poor, moderate, and good. Data were processed and analyzed using SPSS version 20.0. Results: The study revealed an overall mean score of 5.80 ± 1.18 out of 10, with only 4.6% of nurses achieving a good level of knowledge and attitude, 68.7% at a moderate level, and 26.7% falling below the standard. The domain of supportive measures, attitudes, and cultural aspects in pain management showed the highest performance, with a mean score of 7.04 ± 2.48 and 64.5% of participants reaching the good level. In contrast, knowledge and attitudes related to clinical decision-making and pain management practices were limited, with the lowest mean score of 4.30 ± 1.49 and 58% not meeting the standard. Conclusions: Although nurses demonstrated a basic understanding of pain management, targeted training interventions are necessary to enhance clinical decision-making skills and the application of knowledge in practice.